If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 8y = x + -2y Solving 2x + 8y = x + -2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x + 8y = x + -1x + -2y Combine like terms: 2x + -1x = 1x 1x + 8y = x + -1x + -2y Combine like terms: x + -1x = 0 1x + 8y = 0 + -2y 1x + 8y = -2y Add '-8y' to each side of the equation. 1x + 8y + -8y = -2y + -8y Combine like terms: 8y + -8y = 0 1x + 0 = -2y + -8y 1x = -2y + -8y Combine like terms: -2y + -8y = -10y 1x = -10y Divide each side by '1'. x = -10y Simplifying x = -10y
| Y=-5/3-5 | | 2x--2=2 | | 3.4=15.9-5w | | 5x^2+3x=2x(x+6) | | 6p+6=5p+14 | | z+0.9=3.1 | | x(2-12-3m)=-8-2m | | r(1.4+35)=436.60 | | 4x-7=59-7x | | x-1/4=5 | | 2xc+-1c^2x+x=-10+5c | | 4x-3-4=24 | | x+2cx-c^2x=-10+5c | | X^2-25-144=0 | | (6*6-3*3*3)/7 | | (u^4/-2w^2)^2 | | -56=y-49 | | -67=-32n+29 | | 20(b+7)=-20 | | 5b-16=39 | | 76=y/4 | | 2.1x+1.3=-9.2 | | 8.5x-6.5=6.8x+10.0 | | 6(v+3)-2v=2(2v+1)-11 | | 12x-3(3x-6)=2x+2 | | 25=13+8d | | 240=170+5d | | 10f+5= | | -3(l+4)-l-3=-4(l+5)+5 | | 0.8x-0.4(60+x)=0.067(60) | | 0.18y+0.03(y+6000)=810 | | (2x+2)=-4 |